Evaluation of Bovine Myosin Heavy Chain Isoforms and Muscle Fiber Cross-Sectional Area on the Eating Quality of 11 Different Beef Muscles - S. Hene; H. Ness; E. Verrill; P. A. Hammond; C. K. Chun; T. G. O'Quinn; M. D. Chao (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objective of this study was to investigate the contribution of muscle fiber type and size on the eating quality of 11 different beef muscles. Study Description:Eleven different beef muscles were utilized from two separate studies. In study 1, shoulder clod, flank, knuckle, mock tender, top sirloin butt, brisket, eye of round, and ribeye were collected from 10 U.S. Department of Agriculture choice carcasses (n = 80), and each muscle was fabricated into steaks at 2 days postmortem. In study 2, strip loin, tri-tip, and heel were collected from 10 USDA low choice carcasses (n = 30). Myofibrillar proteins were extracted and analyzed by immunoblot to determine muscle fiber type. Cross sectional area (CSA) and muscle fiber diameter were determined under the microscope. An average of 400 fibers per sample were analyzed to determine CSA and muscle fiber diameter. Pearson correlation analysis was conducted to determine the relationship between muscle fiber type, CSA, and diameter with the results for the eating quality of beef as determined by a trained panel that were reported in previous studies. Results:In study 1, there was a positive correlation between fiber type 1 and initial juiciness (r= 0.37;P<0.05), sustained juiciness (r= 0.39;P<0.05) and lipid flavor (r= 0.41;P<0.05). Conversely, there was a negative correlation between fiber type 2A and initial juiciness (r= -0.40;P<0.05) sustained juiciness (r= -0.42;P<0.05), and lipid flavor (r= -0.45;P<0.01). Both studies saw a negative correlation between muscle fiber CSA and diameter with connective tissue content (P<0.05), but positive correlations to overall tenderness (P<0.05). The Bottom Line:This study shows that muscles predominated by type 1 fibers will likely deliver a higher eating quality experience for consumers, while muscles with more glycolytic fibers 2A and 2X will deliver a less favorable eating experience for consumers. On the other hand, these data also demonstrated that larger muscle fiber CSA and diameter are not necessarily a negative eating quality marker as muscles with those characteristics had less connective tissue and had greater tenderness scores.
Keywords: Myosin heavy chain; muscle fiber type; cross-sectional area